Formation and evolution of shale overpressure in deep Wufeng-Longmaxi Formation in southern Sichuan basin and its influence on reservoir pore characteristics - Sun, Shasha; Shi, Zhensheng; Dong, Dazhong; Bai, Wenhua; Wei, Lin; Yin, Jia; Qu, Jiajun (Frontiers in Earth Science, 2024)
In the deep Longmaxi Formation shale gas reservoirs of the southern Sichuan Basin, strong overpressure is universally developed to varying degrees. However, there is currently a lack of indepth research on the formation mechanisms, evolutionary patterns, and the controlling effects on reservoir pore characteristics of strong overpressure. This limitation significantly restricts the evaluation of deep shale gas reservoirs. To address this, typical overpressured shale gas wells in the Yongchuan, Luzhou, and Dazu areas were selected. A comprehensive approach involving well log analysis, fluid inclusion analysis, and numerical simulation was employed to identify the dominant mechanisms behind the formation of strong overpressure and to characterize the pressure evolution during the early continuous burial to the late strong uplift stage. Simultaneously, scanning electron microscopy image analysis, gas adsorption-mercury intrusion, helium porosity testing, and other methods were used to investigate the impact of different degrees of strong overpressure on reservoir pore characteristics. The results indicate that hydrocarbon generation expansion is the dominant mechanism behind the formation of strong overpressure in the study areas. The pressure evolution during the early continuous burial stage is controlled by the processes of kerogen generating oil and retained oil cracking to gas. The reservoir undergoes three stages: normal pressure (Silurian to Early Triassic), overpressure (Early Triassic to Early Jurassic), and strong overpressure (Early Jurassic to Late Cretaceous), corresponding to pressure coefficients of approximately 1.08, 1.56, and 2.09, respectively. In the late strong uplift process, temperature reduction and gas escape lead to a certain adjustment of the early-formed overpressure. The formation pressure decreased from 140.55 MPa to 81.63 MPa, while the trend of pressure coefficients changed from decreasing to increasing and finally maintained strong overpressure at present. Different degrees of strong overpressure have a significant controlling effect on the physical properties of shale reservoirs and the composition of organic matter pores. Deep Wufeng-Longmaxi Formation shale exhibits differences in morphological characteristics, structure and connectivity of organic matter pores. Higher overpressure contributes to the preservation of organic macropores and reservoir porosity. Under strong overpressure development, both deep siliceous shale and clayey shale with abundant organic matter exhibit favorable reservoir properties.